A Collaboration Support Environment for Decision Enhancement in Business Process Improvement - Amiyo, Mercy; Nabukenya, Josephine (Springer, Berlin, Heidelberg., 2011)
Continuous Business Process Improvement (BPI) in light of increased business process agility demand necessitates continuous process analysis and exploration of several improvement alternatives. These activities are knowledge intensive thus require multi-disciplinary skills. Furthermore, the cross-cutting nature of business processes as a result of having several people working on related activities in order to attain business goals necessitates collaboration among stakeholders in any business process improvement effort. However current suites provide limited to no support for this kind of collaboration especially in the decision process involved. In light of this, we designed a decision enhancement studio environment consisting of 4 suites to support collaboration, business process analysis and dissemination of information in order to enhance group decision making and achieve business process agility. Evaluation results from testing sessions at two organisations show that the BPI alternative exploration collaboration process supported by the analysis tools and group support systems provides a BPI decision enhancement studio which is a suitable environment to generate and select a BPI alternative. The BPI Decision enhancement studio is thus useable and useful for collaboration support in the BPI decision process.
Keywords: Business Process Improvement, Business Process Agility, Collaboration Support, Decision Enhancement, Studio